Gambaran Tingkat Pengetahuan Kebersihan Gigi dan Mulut Pada Siswa Pengguna Orthodontik Cekat Sman 1 Rancaekek (Jurnal Terapi Gigi dan Mulut, 2023)
Fixed orthodontics is now widely used by the community, but people often do not realize the risks of using fixed orthodontic appliances that cause oral hygiene problems. The biggest challenge to fixed orthodontic use which leads to problems regarding proper oral hygiene during this treatment is due to the components of the orthodontic appliance. The use of orthodontic appliances among adolescents, especially at the age of 14-17 years, is no longer just a treatment need but has become a lifestyle demand. This study aims to determine the level of knowledge about dental and oral hygiene in fixed orthodontic users at SMAN 1 Rancaekek. This research is descriptive quantitative. Sampling of this research was done by purposive sampling. The way this research works is by giving questionnaires to respondents. The results of this study showed that 34 students used orthodontic subjects where 25 students used fixed orthodontics and 9 students used removable orthodontics. On dental and oral hygiene knowledge, as many as 16 people (64.0%) had good knowledge, 5 subjects had sufficient knowledge (20.0%), and 4 subjects had poor knowledge (16.0%). Behavior of good knowledge as many as 2 people (8.0%), subjects who have moderate knowledge as many as 7 people (28.0%), and subjects who have poor knowledge as many as 16 people (64.0%). It was concluded that knowledge of dental and oral hygiene was categorized as good and knowledge of behavior was classified as poor.